Informational Technology and Its Impact on American Education - Congress of the U.S., Washington, DC. Office of Technology Assessment; Congress of the U.S., Washington, DC. Office of Technology Assessment ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
This study, which examines the extent to which information technology could serve American needs for education and training, documents two basic sets of conclusions: (1) the so-called information revolution is profoundly affecting American education by changing the nature of what needs to be learned, who needs to learn it, who will provide it, and how it will be provided and paid for; and (2) information technology can potentially improve and enrich educational services provided by traditional educational institutions, distribute education and training into new environments such as the home and office, reach new clients such as the handicapped and homebound, and teach job-related skills in the use of technology. This report provides an overview of the issues involved in educational applications of the new technologies, examining both the demands that will be made on education and the opportunities these technologies will afford to meet those demands. A wide variety of new information products and services is examined, including those based on the combined capabilities of computers, telecommunications systems, and video technologies. The effects which information technologies may have on the roles of a broad range of educational providers are also examined. Seventeen case studies of information technology applications are appended. (LMM)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, DC 20402.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Computers; Delivery Systems; Educational Change; Educational Media; Educational Technology; Government Role; School Role; Tables (Data); Technological Advancement; Technology Transfer; Telecommunications; Video Equipment; Information Technology -- United States; Reports, Descriptive; Reports, Research